What Do Micro Price Data Tell Us on the Validity of the New Keynesian Phillips Curve? - Luis Julián Alvarez González (Kiel Institute for the World Economy (IfW), 2007)
The New Keynesian Phillips curve (NKPC) has become the dominant model on inflation dynamics. Moreover, a large body of empirical research has documented in recent years price-setting behaviour at the individual level, which allows the assessment of the microfoundations of pricing models. It is found that a generalised version of the hybrid NKPC of Gali and Gertler (1999) accounts for a number of stylised facts, including rule of thumb price setters, and inflation persistence. Other frequently used versions of the NKPC, such as those that consider full or partial indexation or costs of adjustment, are clearly at odds with micro price evidence.
Keywords: 330; New-Keynesian Phillips Curve; Betriebliche Preispolitik; Preisstatistik; Schätzung; Welt